Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

RESPECTED SIR

Asked by chandant 18th April 2010, 3:34 PM
Answered by Expert
Answer:

Dear Student,

The solution to your problem is as follows -

Let A and B be two non-empty (or non-null) matrices.

By the hypothesis of the question, AB=0

Now, Assume that A is non-singular.

=> A-1 exists.

Therefore, multiply both sides of equation by A-1

=> A-1AB=0

=> B=0

But this is a contradiction to the fact that B is non-empty matrix. Hence A can't be non-singular matrix.

 

Similarly, assume B to be non singular.

=> B-1 exists.

Multiply both sides by B-1,

=> ABB-1=0

=> A=0

Again, this is contradiction to the fact that A is non-empty. Therefore, B can't be non-singular.

 

Regards Topperlearning.

Answered by Expert 22nd April 2010, 11:00 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp